Hydrogeochemical assessment of a coastal aquifer using statistical and geospatial techniques: case study of Mombasa North Coast, Kenya - Temitope, Ezekiel Idowu; Nyadawa, Maurice; K’Orowe, Maurice Odondi (Journal Environmental Earth Science, 2017)
Abstract The geochemistry of a coastal aquifer was assessed using statistical and geospatial analysis tools for the pre-monsoon, rainy and post-monsoon seasons. Data were obtained from both the field and laboratory analysis of water samples. Statistical methods such as correlation coefficients, piper plots, factor analysis and mixing index were used to gain insights into the geochemistry, while geospatial tools were used to create contours to understand the spatial distribution of the measured groundwater parameters of the coastal aquifer. The measured groundwater levels ranged from -0.84 to 30.08 m above mean sea level. The Electrical Conductivities and Total Dissolved Solids values were observed to have perfectly correlated with each other. Groundwater salinities were generally high, as over 94% of the water samples tested exceeded the WHO drinking water limit of 750 lS/cm and 500 mg/l, respectively. The groundwater pH was generally slightly alkaline but could be slightly acidic in the rainy season. The Na?, K?, Mg2?, Cl- and SO4 2- were observed to have high impacts on the geochemistry and also had tendencies to form similar trends. EC, TDS and NaCl values above 1000 mg/l in the groundwater were observed to generally skew towards the ocean during the rainy season. The principal process influencing the geochemistry was found to be seawater intrusion, while mineral dissolutions and rainwater percolation play lesser roles. The aquifer predominantly comprises Na–Cl waters of marine origin. The study shows the growing importance and applicability of integrated statistical and geospatial approaches for better understanding of groundwater and geochemistry of aquifers.
Keywords: Coastal groundwater; Principal component analysis; Correlation analysis; Spatial variation; Piper Seawater mixing index